IMPLIKASI BLOCKCHAIN PADA KECURANGAN AKUNTANSI: TELAAH LITERATUR SISTEMATIS (SLR) - Zafara Luthfiyyah; Totok Dewayanto (Diponegoro Journal of Accounting, 2023)
This research This research aims to identify the implications of Blockchain in preventing accounting fraud and how it works based on published research articles. This research also aims to examine the diversity of results and patterns in terms of recommendations and contributions. Then, this study also explores gaps in science to develop future academic studies.This study uses the systematic literature review (SLR) method to analyze various published articles in academic journals indexed in Scopus published in 2020 to 2023. Articles are filtered using the specified keywords obtained from various top-ranked journals. The SLR method is used to examine topics/themes, results, methodologies, recommendations, and limitations of published articles.The results of the analysis provide evidence that academic studies prove the reliability of blockchain based on its main characteristics, namely cryptographic security, decentralization, and network consensus. In the context of accounting fraud, the use of blockchain can reduce the risk of manipulation of financial data, because every transaction is digitally encrypted and authenticated. Information stored in the blockchain cannot be changed or deleted without the consent of the majority of network participants, thereby minimizing opportunities for fraud.These findings are expected to provide substantial benefits to accounting information, developers in terms of developing Blockchain for organizations and recommend exploring more about the impact of the use of technology in accounting.